FeNC catalyst rich in defects, preparation method of FeNC catalyst and application of FeNC catalyst in acid-base mixed zinc air battery

By using the defect-rich FeNC catalyst synthesized by the co-precipitation method in zinc-vacuo batteries, the problem of slow kinetic activity of single-atom transition metal-N-C catalysts is solved, and efficient acid oxygen reduction and alkaline urea oxidation reactions are achieved, which improves the power density and fast charging performance of zinc-vacuo batteries.

CN119650725APending Publication Date: 2025-03-18INST OF NEW MATERIALS ZHEJIANG UNIV OF TECH PINGHU CITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411819699.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing single-atom transition metal-N-C oxygen reduction catalysts are not conducive to the desorption of intermediates in zinc-empty batteries, resulting in slow kinetic activity.

Method used

The metal organic frame precursor was synthesized by co-precipitation method and pyrolyzed under high temperature conditions to introduce defects to construct defect-rich FeNC catalysts. This method introduces intrinsic defects without destroying the Fe-N4 coordination structure, thereby improving catalytic performance.

Benefits of technology

The defect-rich FeNC catalyst formed has a porous structure and a high specific surface area, which significantly improves the performance of acidic oxygen reduction reaction and alkaline urea oxidation reaction, and achieves high power density and fast charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650725A_ABST
    Figure CN119650725A_ABST
Patent Text Reader

Abstract

The invention provides a defect-rich FeNC catalyst, a preparation method thereof and application of the defect-rich FeNC catalyst in an acid-base mixed zinc air battery, the preparation method comprises the following steps: (1) reacting a reaction solution containing Zn < 2 + >, Fe < 3 + >, a ligand, an etching agent containing a nitrogen element and a solvent to obtain a precipitate which is a metal organic framework precursor; and (2) calcining the metal organic framework precursor in a protective atmosphere to obtain the FeNC catalyst rich in defects. A metal organic framework precursor is synthesized through a simple coprecipitation method, then the structure of the metal organic framework precursor is etched through the etching agent containing the nitrogen element through high-temperature pyrolysis to achieve defect construction, the FeNC catalyst rich in defects is formed, and the FeNC catalyst rich in defects has a porous structure, is high in specific surface area and can be used as a catalyst for preparing the FeNC catalyst rich in defects. More active sites can be easily exposed, and excellent acidic ORR performance and alkaline UOR performance are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy devices and new energy materials, and in particular to a defect-rich FeNC catalyst and a preparation method thereof, and application thereof in an acid-base mixed zinc-air battery. Background Art

[0002] With the intensification of environmental problems and energy crisis, there is an urgent need to develop efficient energy storage and conversion devices. Among them, zinc-air batteries (ZABs) have been widely used due to their low cost, high safety, environmental friendliness and high theoretical energy density (1086Wh·kg -1 ) has attracted much attention. However, its large-scale application still faces multiple challenges. Traditional zinc-air batteries are mainly composed of zinc negative electrode, alkaline electrolyte and air positive electrode. During the discharge process, the zinc negative electrode undergoes oxidation reaction and loses electrons to form zinc ions (Zn 2+ The zinc ions further react with the hydroxide ions (OH - ) reacts to form zincate ions (Zn(OH) 4 2- ), the released electrons are transferred to the air cathode through the external circuit. At the same time, a reduction reaction occurs at the cathode, and oxygen in the air penetrates from the gas diffusion layer into the electrode and is adsorbed on the surface of the air electrode catalyst (i.e., the three-phase interface). Under the action of the catalyst, oxygen is reduced to hydroxide ions (OH - ). The charging process is just the opposite, and the reaction is as follows: Discharge: O 2 +2H 2 O+4e - =4OH - (0.4V vs.SHE) Zn+4OH - =Zn(OH) 4 2- +2e - (-1.25V vs.SHE) Charge: 4OH - =O 2 +2H 2 O+4e - (0.4V vs.SHE) Zn(OH) 4 2- +2e - =Zn+4OH - (-1.25V vs.SHE) On the one hand, due to the narrow voltage window of alkaline electrolyte, the actual discharge voltage of zinc-air batteries is only about 1.2V, which leads to low power density and energy density; on the other hand, during the charging process, the oxygen evolution reaction (OER) has a high thermodynamic potential (1.23V), which causes energy loss, resulting in a higher charging voltage (about 2V), and the energy efficiency is reduced to about 60%, which seriously restricts the practical application prospects of zinc-air batteries.

[0003] In contrast, the standard potential of oxygen reduction reaction (ORR) in acidic electrolyte (1.23 V vs. SHE) is higher than that in alkaline electrolyte (0.4 V vs. SHE), which helps to broaden the voltage window of ZAB. However, the acidic environment will cause severe corrosion of the zinc anode and the generation of a large amount of hydrogen, which not only reduces the battery performance but also accelerates the deactivation of the catalyst.

[0004] To address this problem, a study proposed a strategy to decouple the electrolyte into an acidic cathode electrolyte and an alkaline anode electrolyte using a bipolar membrane. This method effectively alleviated the corrosion problem of the zinc negative electrode and successfully increased the operating voltage of ZAB to 2V, achieving high power and high energy density. However, the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) have different requirements for the reaction environment and active sites, which makes it a major challenge to achieve high activity of both reactions on the same electrode.

[0005] Recent studies have shown that the electrocatalytic oxidation reactions of some small-molecule organic compounds (such as urea, alcohols, and glucose) are thermodynamically more advantageous than the oxygen evolution reaction (OER). Among these reactions, the urea oxidation reaction (UOR) has attracted widespread attention due to its low theoretical thermodynamic potential (0.37V), wide availability, low cost, and environmental friendliness. At the same time, untreated urea-rich industrial and domestic wastewater can lead to eutrophication of water resources, while ammonia and nitrates produced by urea decomposition are also harmful to the environment and human health. Among the existing urea pollution treatment methods, the electro-oxidation method shows obvious superiority due to its high efficiency and low cost. Therefore, replacing OER with UOR is expected to achieve efficient charging while purifying urea wastewater.

[0006] However, even so, the optimization of energy efficiency and voltage window is still limited by the inherent slow kinetics of the cathode acidic oxygen reduction reaction. At present, precious metal catalysts show excellent catalytic performance in ORR, but their high cost and poor stability seriously hinder the large-scale promotion of zinc-air batteries. Therefore, the development of high-performance, low-cost non-precious metal catalysts has become a key driving force for the development of ZAB. Among the many catalysts, single-atom transition metal-NC (TM = Fe, Co, Cu, Ni, Mn) is considered to be an excellent class of oxygen reduction catalysts due to its good conductivity, high stability, and large specific surface area. However, TM-N4 The electron density distribution with high symmetry in some parts is not conducive to the desorption of intermediates, resulting in slow kinetic activity. Adjusting the defect chemistry in the carbon matrix is ​​believed to induce TM-N x An effective way to redistribute site charge to promote the ORR process. Summary of the invention

[0007] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a defect-rich FeNC catalyst and a preparation method thereof, and application in an acid-base mixed zinc-air battery, so as to solve the problem that the existing single-atom transition metal-NC oxygen reduction catalyst is not conducive to the desorption of intermediates when applied to zinc-air batteries, resulting in slow kinetic activity.

[0008] To achieve the above objectives and other related objectives, the present invention provides a method for preparing a defect-rich FeNC catalyst, comprising: (1) Containing Zn 2+ , Fe 3+ , a ligand, an etchant containing nitrogen and a reaction solution of a solvent to react, and the resulting precipitate is a metal organic framework precursor; (2) calcining the metal organic framework precursor under a protective atmosphere to obtain a defect-rich FeNC catalyst.

[0009] The present invention synthesizes a metal organic framework precursor by a simple coprecipitation method, and then etches the metal organic framework precursor structure containing nitrogen by high temperature pyrolysis to achieve defect construction and form a defect-rich FeNC catalyst. This process aims to precisely control the etching conditions without destroying the Fe-N 4 Under the premise of the coordination structure, intrinsic defects are introduced to improve the catalytic performance. Specifically, zinc salt, iron salt, ligand and etchant are first synthesized by self-assembly to form a metal organic framework structure with transition metal. The etchant participates in the reaction under high temperature conditions, and the thermal decomposition product reacts with the nitrogen source of the metal organic framework precursor, resulting in the elimination of part of the nitrogen element and promoting the rearrangement of carbon atoms and iron ions. This process can retain the Fe-N while removing some nitrogen atoms in the metal organic framework precursor. 4 The coordination structure of FeNC catalysts with defective carbon was generated, thus enhancing the Fe-N 4 The catalytic activity of the site.

[0010] Preferably, in step (1), the Zn 2+ with Fe 3+ The molar ratio of the substances is (20~25):2.

[0011] Preferably, the Zn 2+ It is added in the form of a zinc salt selected from Zn(NO3 ) 2 6H 2 O、ZnSO 4 7H 2 O、Zn(CH 3 COO 2 ·2H 2 O and ZnCl 2 6H 2 One or more of O.

[0012] Preferably, the Fe 3+ Add in the form of an iron salt, the iron salt is selected from Fe(NO 3 ) 3 9H 2 O, Fe 2 (SO 4 ) 3 9H 2 O, FeCl 3 6H 2 One or more of O.

[0013] Preferably, in step (1), the ligand is 2-methylimidazole.

[0014] Preferably, in step (1), the Zn 2+ with Fe 3+ The ratio of the sum of the amounts of substance to the amount of substance of the ligand is (8~12):1.

[0015] Preferably, in step (1), the etchant is selected from urea (CO(NH 2 ) 2 ), methylamine (CH 3 NH 2 ), ethylamine (C 2 H 5 NH 2 ), allylamine (C 3 H 5 NO) and amino acids (NH 2 CH 2 COOH) or more.

[0016] Preferably, in step (1), the solvent is methanol.

[0017] Preferably, in step (1), the molar ratio of the ligand to the etchant is (20-25):2.

[0018] Preferably, in step (2), the calcination temperature is 850-1000°C.

[0019] The present invention also provides a defect-rich FeNC catalyst prepared by the above preparation method.

[0020] The present invention also provides an application of the defect-rich FeNC catalyst in an acid-base mixed zinc-air battery.

[0021] The present invention also provides a urea-assisted acid-base mixed zinc-air battery (UR-AA-HZAB), which comprises a shell, a cation exchange membrane, a dual air cathode and a zinc anode, wherein the dual air cathode comprises a modified discharge cathode and a modified charge cathode, the shell is separated by the cation exchange membrane to form an acidic chamber and an alkaline chamber, the discharge cathode is placed in the acidic chamber, the charge cathode is placed in the alkaline chamber, the surfaces of the modified discharge cathode and the modified charge cathode are coated with a coating containing the above-mentioned defect-rich FeNC catalyst, the acidic chamber is filled with an acidic electrolyte, the alkaline chamber is filled with an alkaline electrolyte, and the alkaline electrolyte contains urea.

[0022] Preferably, the acidic electrolyte is 2 to 3 M H 2 SO 4 The alkaline electrolyte contains the following components: 5-6M KOH, 0.2-0.3M Zn(Ac) 2 and 0.3-0.4M urea.

[0023] Preferably, the modified discharge cathode is prepared by dripping a catalyst dispersion onto the surface of the discharge cathode to form a catalyst coating; and the modified charge cathode is prepared by dripping a catalyst dispersion onto the surface of the charge cathode to form a catalyst coating.

[0024] Preferably, the catalyst dispersion is formed by dispersing the defect-rich FeNC catalyst in a mixed solution of Nafion, ethanol and water. Nafion is a perfluorosulfonic acid polymer solution used as a binder.

[0025] Preferably, the concentration of the defect-rich FeNC catalyst in the catalyst dispersion is 4-6 mg / mL.

[0026] As described above, the present invention has the following beneficial effects: (1) The present invention synthesizes a metal organic framework precursor by a simple co-precipitation method, and then etches the metal organic framework precursor structure by high temperature pyrolysis with an etchant containing nitrogen element to achieve defect construction, thereby forming a defect-rich FeNC catalyst. The defect-rich FeNC catalyst has a porous structure and a high specific surface area, which is conducive to exposing more active sites and exhibits excellent acidic ORR performance and alkaline UOR performance; (2) The urea-assisted acid-base hybrid zinc-air battery of the present invention broadens the voltage window by the acid-base pH gradient, thereby achieving high power density. By decoupling the dual air cathode into a modified discharge cathode and a modified charging cathode, respectively, whose surfaces contain a coating of the defect-rich FeNC catalyst, catalyzing the acidic ORR and alkaline UOR reactions, and replacing OER with UOR with low thermodynamic potential, the charging voltage can be significantly reduced, fast charging at high current density can be achieved, and the stability of the hybrid zinc-air battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Shown are TEM images of FeNC@D of Example 1 (a) and FeNC of Comparative Example 1 (b).

[0028] Figure 2 Shown are nitrogen adsorption-desorption graphs of FeNC@D of Example 1 and FeNC of Comparative Example 1.

[0029] Figure 3 Shown are the ORR polarization curves of FeNC@D of Example 1 and FeNC of Comparative Example 1.

[0030] Figure 4 Shown are the UOR and OER polarization curves of FeNC@D of Example 1 and FeNC of Comparative Example 1.

[0031] Figure 5 Shown is a schematic diagram of the structure of a urea-assisted rechargeable acid-base hybrid zinc-air battery.

[0032] Figure 6 Shown are the power density curves of the urea-assisted acid-base hybrid zinc-air battery (UR-AA-HZAB) prepared in Example 1 and the traditional zinc-air battery (ZABs) prepared in Comparative Example 1.

[0033] Figure 7 The results show that the urea-assisted acid-base mixed zinc-air battery (UR-AA-HZAB) prepared in Example 1 and the conventional zinc-air battery (ZABs) prepared in Comparative Example 1 have a high charge / discharge rate at 50 mA cm -2 Charging cycle curves at high current density. DETAILED DESCRIPTION

[0034] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0035] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0036] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0037] Example 1 The present application embodiment provides a method for preparing a defect-rich FeNC catalyst, comprising the following steps: (1) Synthesis of FeZn@Urea-MIM powder: 4.6 mmol Zn(NO 3 ) 2 6H 2 O and 0.4mmol Fe(NO 3 ) 3 9H 2 O was dissolved in 60 mL of methanol and ultrasonicated for 10 min, which was marked as solution A; 46 mmol of 2-methylimidazole and 4 mmol of urea were dissolved in 60 mL of anhydrous methanol and ultrasonicated for 10 min, which was marked as solution B. Solution A and solution B were quickly mixed and stirred at room temperature for 8 hours. The mixed solution was washed with anhydrous methanol three times and then centrifuged. After vacuum drying at 60 ° C overnight, the metal organic framework precursor was obtained. The sample was recorded as FeZn@Urea-MIM powder; (2) Synthesis of FeNC@D catalyst: 200 mg of FeZn@Urea-MIM precursor powder was weighed and placed in a tubular furnace. Nitrogen was passed through the furnace for 30 min to exhaust the air. The temperature was then raised to 950°C at a rate of 5°C / min in a nitrogen atmosphere and maintained at 950°C for 3 h. The temperature was then naturally cooled to room temperature under nitrogen protection to obtain a defect-rich FeNC catalyst. The sample was recorded as FeNC@D.

[0038] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no urea is added to Solution B, and the other processes are exactly the same. The obtained sample is recorded as FeNC.

[0039] The FeNC@D prepared in Example 1 and the FeNC prepared in Comparative Example 1 were characterized.

[0040] like Figure 1 As shown in the figure, both FeNC@D and FeNC catalysts present a polyhedral structure with a particle size of about 150 nm and do not contain metal clusters. Figure 1 Obvious pore structures can be seen in the FeNC@D material in a, indicating that FeNC@D contains more defects than FeNC.

[0041] Figure 2 The nitrogen adsorption-desorption analysis of FeNC@D and FeNC shows that both FeNC@D and FeNC show type I isotherm adsorption curves, indicating the formation of rich microporous channel structures, which is attributed to the pyrolysis of organic ligands at high temperatures. It is worth noting that FeNC@D shows 1294.22 m 2 The high specific surface area of ​​1.377 million tons / g and the hierarchical micropore-mesopore structure help to expose more catalytic active sites and promote the contact between reactants and active sites, thereby improving the catalytic efficiency.

[0042] Electrochemical performance test Figure 3 The ORR polarization curves of FeNC and FeNC@D. Figure 3 It can be seen that the electrocatalytic oxygen reduction reaction (ORR) activity of FeNC@D is 2 Saturated 0.05MH 2 SO 4 The electrolyte was evaluated using a three-electrode system consisting of a carbon rod (counter electrode), Ag / AgCl (reference electrode), and catalyst ink droplets on carbon paper (working electrode). Figure 3 ), the half-wave potential of FeNC@D is 0.81 V, which is significantly higher than that of FeNC (0.77 V), which may be because FeNC@D contains more defects and exposes more active sites.

[0043] Figure 4 UOR and OER polarization curves of FeNC@D.

[0044] Considering that human urine contains 2-2.5 wt% urea (about 0.33 M), in order to simulate urea-rich wastewater (urine), 0.33 M urea was added to 1 M KOH electrolyte to evaluate the urea oxidation reaction (UOR) performance. Figure 4 As shown, FeNC@D at 10 mA cm -2 The UOR potential of 1.347 V was achieved at a current density of 1.5 volts, which is 158 mV lower than the potential of the oxygen evolution reaction (OER) at the same current density.-2 At a high current density of 1.3 Å, the UOR potential of FeNC@DF is 174 mV lower than the OER potential. This indicates that replacing UOR with OER can help improve the fast charging performance of zinc-air batteries (ZABs).

[0045] Application Example 1 The present application also provides a method Figure 5 The urea-assisted acid-base mixed zinc-air battery (UR-AA-HZAB) shown in the figure comprises a shell, a cation exchange membrane (CMB), a dual air cathode and a zinc anode, wherein the dual air cathode comprises a modified discharge cathode and a modified charge cathode, the shell is separated by a cation exchange membrane to form an acidic chamber and an alkaline chamber, the discharge cathode is placed in the acidic chamber, the charge cathode is placed in the alkaline chamber, the modified discharge cathode and the modified charge cathode are coated with a coating containing the defect-rich FeNC catalyst prepared in Example 1, the acidic chamber is filled with an acidic electrolyte, and the acidic electrolyte is 2M H 2 SO 4 Solution; the alkaline chamber is filled with an alkaline electrolyte, the alkaline electrolyte comprising the following components at concentrations: 6M KOH, 0.2M Zn(Ac) 2 and 0.33 M urea.

[0046] The modified discharge cathode is prepared by dripping a catalyst dispersion on the surface of the discharge cathode to form a catalyst coating; the modified charge cathode is prepared by dripping a catalyst dispersion on the surface of the charge cathode to form a catalyst coating, the catalyst dispersion is formed by dispersing the defect-rich FeNC catalyst in a mixed solution of Nafion, ethanol and water, and the concentration of the defect-rich FeNC catalyst in the catalyst dispersion is 5 mg / mL.

[0047] The design principle of urea-assisted acid-base mixed zinc-air battery is as follows: During the discharge process of UR-AA-HZAB, the zinc anode in the alkaline electrolyte is oxidized to Zn(OH) 4 2- , releasing two electrons. These electrons are transferred to the acid electrolyte through an external circuit and undergo an oxygen reduction reaction (ORR) with oxygen in the air. +Ions migrate from the alkaline electrolyte to the anolyte through the cation exchange membrane. The theoretical voltage of UR-AA-HZAB can reach 2.48V, which is significantly higher than the 1.65V of conventional ZAB. This is mainly attributed to the higher standard potential provided by ORR in acidic electrolyte (1.23V vs.SHE) compared to the potential in alkaline electrolyte (0.4V vs.SHE). In addition, during the charging process, the zinc deposition reaction is paired with the urea oxidation reaction (UOR, -0.46V vs.SHE) with a lower oxidation potential, replacing the oxygen evolution reaction (OER, 0.4V vs.SHE) in the alkaline cathode. In theory, UR-AA-HZAB can be charged at a lower voltage (0.79V), much lower than the 1.65V of conventional ZAB. Therefore, the constructed UR-AA-HZAB can theoretically achieve high discharge voltage and low charging voltage.

[0048] Application Comparative Example 1 The defect-rich FeNC catalyst prepared in Example 1 was used to prepare a conventional zinc-air battery (ZABs) as follows: 2 The FeNC@D catalyst carbon paper prepared in Example 1 was used as the cathode of the ORR and OER bifunctional catalyst and paired with a polished zinc anode in 0.2 M Zn(Ac) 2 and 6.0M KOH alkaline electrolyte to form a zinc-air battery.

[0049] The performance of the urea-assisted acid-base mixed zinc-air battery (UR-AA-HZAB) prepared in Example 1 and the conventional zinc-air battery (ZABs) prepared in Comparative Example 1 were compared. Figure 6 and Figure 7 shown.

[0050] Figure 6 The LSV curves in Figure 2 show that UR-AA-HZAB has a higher discharge voltage (2.1 V), which leads to a higher power density (360 mW cm -2 ), which is better than the traditional ZAB (155mW cm -2 ) more than twice.

[0051] Figure 7 It is shown that UR-AA-HZAB can -2 ) can not only run stably for 220h, exceeding the 140h of traditional ZAB, but its fast charging energy efficiency can reach about 95%.

[0052] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a defect-rich FeNC catalyst, characterized in that: include: (1) Containing Zn 2+ , Fe 3+ , a ligand, an etchant containing nitrogen and a reaction solution of a solvent to react, and the resulting precipitate is a metal organic framework precursor; (2) calcining the metal organic framework precursor under a protective atmosphere to obtain a defect-rich FeNC catalyst.

2. The preparation method according to claim 1, characterized in that: In step (1), the Zn 2+ with Fe 3+ The molar ratio of the substance is (20-25):2; the ligand is 2-methylimidazole; the Zn 2+ with Fe 3+ The ratio of the sum of the amounts of substance to the amount of substance of the ligand is (8~12):

1.

3. The preparation method according to claim 2, characterized in that: In step (1), the etchant is selected from one or more of urea, ethylamine, acrylamine and amino acid; and the solvent is methanol.

4. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of the ligand to the etchant is (20-25):

2.

5. The preparation method according to claim 1, characterized in that: In step (2), the calcination temperature is 850-1000°C.

6. A defect-rich FeNC catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the defect-rich FeNC catalyst as claimed in claim 6 in an acid-base mixed zinc-air battery.

8. An acid-base mixed zinc-air battery, characterized in that: The acid-base mixed zinc-air battery comprises a shell, a cation exchange membrane, a dual air cathode and a zinc anode, wherein the dual air cathode comprises a modified discharge cathode and a modified charge cathode, the shell is separated by a cation exchange membrane to form an acidic chamber and an alkaline chamber, the discharge cathode is placed in the acidic chamber, the charge cathode is placed in the alkaline chamber, the surfaces of the modified discharge cathode and the modified charge cathode are coated with a coating containing the defect-rich FeNC catalyst as described in claim 6, the acidic chamber is filled with an acidic electrolyte, the alkaline chamber is filled with an alkaline electrolyte, and the alkaline electrolyte contains urea.

9. The acid-base mixed zinc-air battery according to claim 8, characterized in that: The acidic electrolyte is a 2-3M H2SO4 solution, and the alkaline electrolyte contains the following components in concentration: 5-6M KOH, 0.2-0.3M Zn(Ac)2, and 0.3-0.4M urea.

10. The acid-base mixed zinc-air battery according to claim 8, characterized in that: The modified discharge cathode is prepared by dripping a catalyst dispersion on the surface of the discharge cathode to form a catalyst coating; The modified charging cathode is prepared by dripping a catalyst dispersion on the surface of the charging cathode to form a catalyst coating, wherein the catalyst dispersion is formed by dispersing the defect-rich FeNC catalyst in a mixed solution of Nafion, ethanol and water, and the concentration of the defect-rich FeNC catalyst in the catalyst dispersion is 4-6 mg / mL.